Distrust Spillover in Sharing Accommodation: Evidence From Airbnb in Beijing - Xin Jin; Bo Wang; Ning Ma (SAGE Open)
The expansion of sharing accommodation has raised concerns about consumer distrust. Scholars have increasingly focused on studying the negative effects of distrust spillover in this field. This study aimed to analyze the factors influencing distrust spillover, understand its mechanism, and propose effective methods to prevent it. Based on triadic reciprocal determinism and trust transfer theory, the study developed a model of distrust origins, transmission, and spillover. Beijing Airbnb listings data were collected and analyzed using sentiment analysis, machine learning, and econometric statistics in English and Chinese languages. The findings revealed that guests’ distrust results in two types of spillover: affecting individual repurchase decisions and influencing potential consumers consumption intentions. And the study identified a window period threshold for the spillover of guests’ distrust, where experiencing more than three failure experiences lead to a spillover effect on consumer decision-making. By monitoring consumer failure experiences, controlling the window period, and addressing negative impressions of hosts, the impact of distrust spillover could be mitigated. This study served as a clue for hosts and platforms in the sharing accommodation industry, highlighting the dual spillover effects of guests’ distrust. It also provided strategic support for the development of sharing accommodations and contributed to optimizing service.